MELACAK SEJARAH DAN PENGGUNAAN NAGHAM ARABI DI INDONESIA - Noorhidayati, Salamah; Farihin, Hibbi; Aziz, Thoriqul (QOF, 2021)
There are two elements of art in the Quran which come from two different sources. First, from the internals of Quran, such as language style, diction, correlation between verses, and others. Second, from the external of the Quran, such as how to read, rhythm (nagham/langgam), and others. This study focusedd on the second part, namely the rhythm (nagham) in Quranic verses and more specifically on the Arabic rhythm of Arab. The history of the existence of the rhythm in Quran verses in the Islamic world has existed since Islam appeared in the world. However, in Indonesia, the history of Arabic rhythm is still confusing. Therefore, this study aimed to trace the early history of the entry and use of the Arabic rhythm in Indonesia. This research used descriptive-historical method. This research found the early history of the emergence of the nagham of Arab in Indonesia which is inseparable from the network of archipelago scholars with the Middle East in the twentieth century. Nagham of Arab has continued to develop since the establishment of Jam'iyyatu al-Qurra’ wa al-Huffa>z (JQH) in the 1950s and the presence of PTIQ and IIQ. Arabic rhythm is used in Indonesia in various occasions, such as being used as a competition (MTQ), reading at the beginning of every event, reading of Quran (tadarus), and Quranic recitation concert.